Events in the cytoplasm during male meiosis in Lilium. - Bird, J; Porter, E; Dickinson, H (1983)
An electron microscopic investigation of the events associated with meiosis in Lilium has revealed a number of changes in both the organellar population and the other cytoplasmic components. Ribosome numbers decrease significantly in early prophase and are later replenished in the tetrads, a process most likely involving the newly arising cytoplasmic nucleoloids. The organelles show a cycle of de- and redifferentiation and later in meiosis unusual internal structures can be seen before these organelles enter a division phase resulting in increased numbers. The localization of acid phosphatase during these changes has also been studied using electron microscopic cytochemical methods. In early prophase, considerable amounts of acid phosphatase are found in vesicles scattered through the cytoplasm; activity is also found in association with most membranous surfaces and often markedly associated with condensing mitochondria. Later in prophase the enzyme activity decreases to normal levels. Electron microscopic autoradiography revealed that DNA is synthesized in both plastids and mitochondria during meiotic prophase with activity reaching a peak during zygotene and ceasing by diakinesis and tetrad formation. These changes point to a certain independence of organelles from nuclear control during meiosis. The events are also evaluated in relation to a cytoplasmic clearing mechanism, which may occur in preparation for the changeover from sporophytic to gametophytic control and the development of gametes.